Short-term outcome of patients with adult IgA vasculitis: a single-center experience - Hočevar, Alojzija; Ostrovršnik, Jaka; Jurčić, Vesna; Tomšič, Matija; Rotar, Žiga (Frontiers in Medicine, 2023)
Background: Follow-up data on IgA vasculitis (IgAV) in adults are scarce. We aimed to investigate the outcome of adult IgAV in a well-defined cohort.Methods: Data from histologically proven patients diagnosed between January 2010 and July 2022 with an at least 3-month follow-up were analysed. The frequency and type of relapses, and the information on kidney function were extracted. Risk factors for IgAV relapse and decline of renal function were studied using the Cox hazards regression analysis. Mortality in IgAV was assessed using the Kaplan-Meier analysis and the standardized mortality ratio (SMR).Results: 265 patients were followed for a median of 24 months. At baseline, 38.9%, 29.8%, 44.5% had articular, gastrointestinal, and renal involvement, respectively. Initially, 189 (71.3%) patients received systemic glucocorticoids, and 32 (12.1%) received an additional immunomodulator. During follow-up 42 (15.8%) patients relapsed. Relapses were more common in younger patients (HR 1.03 (95%CI 1.01; 1.05) and those without baseline glucocorticoid treatment (HR 3.70 (95%CI 2.0; 6.67)).. Furthermore, 74 (27.9%) patients had persistent abnormal urinalysis, and a substantial (≥20%) decline of glomerular filtration rate (eGFR) was recorded in 41 (15.5%) patients. The factors associated with persistent abnormal urinalysis persistently abnormal urine analysis were an absence of IgAV joint involvement and baseline immunomodulatory treatment. Pre-existent chronic kidney disease and heart failure were associated with eGFR decline. The overall SMR was 1.4 (95%CI 1.14; 1.71) compared to the Slovenian general population.Conclusions: 15% of adults experienced IgAV relapseIgAV relapses occurred in 15% of patients, with younger patients with symptomatically managed IgAV experiencing it more frequently. Heart failure emerged as a predictor of persistent abnormal urinalysis persistent urinary aberrations and decline of eGFR. Adults with IgAV had an increased mortality compared to general population.